On the key role of Cu on the oxidation behavior of Cu–Ni–Fe based anodes for Al electrolysis. (December 2015) - Gavrilova, E.; Goupil, G.; Davis, B.; Guay, D.; Roué, L.
Highlights: Cu–Ni–Fe alloys were produced by high-energy ball milling with different Cu contents. Their oxidation behavior was studied at 700 °C under O2 atmosphere. Their electrochemical behavior was studied in KF–AlF3-based electrolyte at 700 °C The key role of Cu in the formation of the NiFe2O4 phase was highlighted. Abstract: In order to prepare anode materials for testing for Al electrolysis, monophased Cu–Ni–Fe alloys were produced by high-energy ball milling with different Cu contents (65, 55 and 45 wt%) and a Ni/Fe mass ratio fixed at 1.33. A Cu-free alloy (57Ni43Fe) was also evaluated for comparison. Their oxidation behavior was studied at 700 °C under O2 atmosphere and in Al electrolysis conditions. Under both conditions, it is shown that the presence of CuO in the outer layer is critical for the formation of an inner protective layer of NiFe2 O4 and depends critically on the Cu content of the alloy.